Pengaruh Sikat dan Pasta Gigi Anak Terhadap Kekasaran Permukaan SIK dan Kompomer (Penelitian) - Deviyanti Pratiwi; Syifa Annisa (Jurnal Kedokteran Gigi Terpadu, 2019)
Background: Surface roughness at restoration and the tooth surface can be caused by the routine activity of brushing and abrasive materials contained in toothpaste. Surface roughness causes bacterial colonization and affects oral and dental health. Objective: This study aimed to determine the effect of the use of a toothbrush and toothpaste child against GIC and compomer surface roughness. Method: This study was an experimental laboratory. Comparison of surface roughness using surface roughness tester before and after brushing on 2 group samples of GIC and compomer with speed of 1 mm/sec and a load of 200 grams, which is assumed as the pressure when brushing teeth. Results: The results of paired t-test calculations on compomer before tooth brushing were 0.3468 ± 0.8801 μm and after brushing was 2.9528 ± 0.7252 μm with p = 0.001 (p <0.05). While the results of the roughness test data at the surface of SIK before tooth brushing was 0.7314 ± 0.3810 µm and after brushing was 3.2102 ± 0.9522 µm with p = 0.003 (p <0.05). The result showed that there is a significant difference in surface roughness of SIK and compomer before and after brushing significantly. Unpaired t-test was performed on both test groups (p = 0.058: p> 0.05) showed no significant difference between surface roughness at SIK and compomer restorations Conclusion: The use of abrasive in toothpaste and tooth brushing routine caused surface roughness at GIC and Compomer restorations. The surface roughness value on both of the restoration materials was higher after simulating tooth brushing.